Identifying Language Learning Strategies for Children with Communication Disorder in New Normal Era - Bintoro, Totok; Fahrurrozi; Murni Winarsih (Universitas Pendidikan Ganesha, 2022)
Practicing language skills for children with communication disorders is in dire need of optimally tested strategies. This study aims to explore the perceptions of inclusive primary school teachers on the implementation of language learning strategies for children with communication disorders in the New Normal era. Data was collected through a survey of 137 teachers and semi-structured interviews with 24 inclusive primary school teachers. Data analysis used quantitative surveys and thematic analysis of qualitative data. The results of the analysis found four main themes namely, listening skills learning strategies, speaking skills learning strategies, reading skills learning strategies, and writing skills learning strategies. The results of this study indicate that language learning strategies for children with communication disorders vary widely from listening to voices, listening news, writing by dictation, reading pictures, appreciating drama, telling stories, singing, and many more. However, all language skills learning strategies for children with communication disorders will not succeed without the involvement of teachers, parents, and the surrounding community. We all have to realize that following children's development is the most important thing to realize optimal child development. Parents must have quality time and the ability to detect children's growth and development, especially children's language and communication development. This research can also be a reference for future researchers to develop a learning model that is appropriate for children with communication disorders.